IMPROVEMENT OF ECONOMIC RELATIONS IN THE MARKET OF EDUCATIONAL SERVICES - Saidkulova Firuza Farmonovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides analytical information on ways to improve economic relations in the market of educational services, competitiveness of education, ways to develop economic communication in higher education institutions.